Restoring B cell intrinsic tolerance to lupus autoimmunity: a rational strategy for lupus treatment - Shai, Shreya Desikan; Chavan, Sailee Vijay; Huan, Elaine Zi; Kalin, Peter M.; Feuerman, Miriam; Roman, Christopher A. J.; Huan, Chongmin (Frontiers in Immunology, 2026)
Systemic Lupus Erythematosus (SLE or lupus) is a chronic autoimmune disease characterized and driven by anti-nuclear antibodies, most prominently anti-double-stranded (ds) DNA IgGs. Lupus remains a serious clinical challenge largely because available medications lack specificity to lupus autoimmunity, unavoidably impairing normal immune responses and often harming other important body functions. Reinforcement of immune tolerance has a great potential for selective suppression of lupus autoimmunity. However, despite extensive efforts, satisfactory clinical outcomes have not yet been achieved. Here, we review relevant literature on the approaches that reinforce immune tolerance for lupus treatment and classify them into following categories based on their mechanisms of action: (1) directly blocking anti-dsDNA antibodies, (2) leveraging regulatory T cell-regulated B cell extrinsic tolerance, and (3) reinforcing B cell intrinsic tolerance. B cell intrinsic tolerance contains various “built-in” self-protective mechanisms that prevent B cell autoimmunity. In lupus patients, impaired B cell intrinsic tolerance to lupus autoimmunity is a root cause of disease development. However, due to the poorly understood tolerance mechanisms, few publications have studied therapeutic approaches that restore B cell intrinsic tolerance to lupus autoimmunity for physiological suppression of disease. To facilitate the development of such approaches, this review concludes by emphasizing a discussion of B cell intrinsic tolerance to lupus autoimmunity, including our recent finding of a B cell intrinsic tolerance mechanism that was required to prevent lupus pathogenesis and could be pharmacologically restored to selectively suppress lupus autoimmunity in a preclinical model.